Compensation consultants: Does reputation matter? - Canil, Jean; Karpavičius, Sigitas (Journal of Corporate Finance, 2020)
In this paper, we analyze the role of hiring a reputable compensation consultant for firms wanting to secure affirmative Say on Pay (SoP) votes. We provide evidence that reputation influences shareholders voting behavior positively when CEO pay is excessive and when peer CEOs are paid less. We employ two methods to account for endogeneity, instrumental variables as well as examining firms switching up to more reputable compensation consultants. Our results are robust with respect to CEO pay and complexity as well as fees and alternate measures of reputation. Firms concerned with the negative feedback associated with negative SoP votes should factor reputation in their decision to hire consultants, especially if trying to adopt compensation packages that may appear excessive.